A Spotlight on T Lymphocytes in Duchenne Muscular Dystrophy—Not Just a Muscle Defect - Chantal A. Coles; Ian Woodcock; Daniel G. Pellicci; Peter J. Houweling (Biomedicines, 2022)
The lack of dystrophin in Duchenne muscular dystrophy (DMD) results in membrane fragility resulting in contraction-induced muscle damage and subsequent inflammation. The impact of inflammation is profound, resulting in fibrosis of skeletal muscle, the diaphragm and heart, which contributes to muscle weakness, reduced quality of life and premature death. To date, the innate immune system has been the major focus in individuals with DMD, and our understanding of the adaptive immune system, specifically T cells, is limited. Targeting the immune system has been the focus of multiple clinical trials for DMD and is considered a vital step in the development of better treatments. However, we must first have a complete picture of the involvement of the immune systems in dystrophic muscle disease to better understand how inflammation influences disease progression and severity. This review focuses on the role of T cells in DMD, highlighting the importance of looking beyond skeletal muscle when considering how the loss of dystrophin impacts disease progression. Finally, we propose that targeting T cells is a potential novel therapeutic in the treatment of DMD.